Rancang Bangun Rumah Budi Daya Jamur Tiram Berbasis Internet Of Things di Desa Argumulyo, Yogyakarta - Yanuar Agung Fadlullah; Khakam Ma'ruf (Eastasouth Institute, 2023)
Argomulyo Village is one of the areas that is the center of the oyster mushroom industry. The current condition of the mushroom cultivation system in Argomulyo Village still uses a conventional system, causing various problems. For example, there is no automatic room monitoring and controlling system and the watering method is still manual. This has an impact on mushroom growth because the temperature and humidity of the barn are not maintained, thus reducing cultivation productivity. Therefore, the author offers an IoT-based mushroom cultivation technology innovation for the Argumulyo Village community. The research method used is the literature study method sourced from valid journal and print media data in accordance with the research objectives. The technology is designed by utilizing solar panels as an energy source and equipped with automatic controls that can be controlled with a Smartphone to make operation easier. Features in the application are monitoring temperature, humidity, watering, and heating the room. The application of technology is expected to improve the economy of oyster mushroom cultivators with more modern cultivation solutions.